Nightmare frequency in last trimester of pregnancy. Issue 1 (December 2016) - Schredl, Michael; Gilles, Maria; Wolf, Isabell; Peus, Verena; Scharnholz, Barbara; Sütterlin, Marc; Deuschle, Michael
Abstract Background Pregnancy-related dreams are often found in pregnant women but also the number of negatively toned dreams seems to be increased in this challenging phase of a woman's life. Methods Nightmare frequency and subjectively experienced stress was elicited via questionnaires. The mothers-to-be were approached during their application visit about 4–8 weeks prior to delivery in three obstetric hospitals. The present analysis included 406 women aged 16–40 years in the last trimester of their pregnancy. Women with severe somatic illnesses and/or psychiatric disorders were excluded. The representative sample included 496 women (age range: 14–93 years.). Results The findings clearly indicate that pregnant women report nightmares more often compared to a representative sample and that nightmare frequency is closely related to subjectively experienced stress during daytime. Moreover, baby-related dreams were correlated with nightmare frequency but not with day-time stress. Conclusions Future studies should investigate the prevalence of nightmare disorders in pregnancy and study whether brief interventions like Imagery Rehearsal Therapy are beneficial for pregnant women suffering from nightmares.